Managing the Challenging Dual Role of Being a Population Health Doctoral Student and Having a Life Outside of School - A Commentary - Amber Canto (University of North Florida, 2015)
Being a successful doctoral student is challenged by life forces such as job, family, and balancing other life commitments. In this paper I comment on these challenges and offer some thoughts on finding a balance that works for me. Keys to meeting this challenge include learning to say "no," finding time for important things, establishing new expectations, acknowledging new and multiple roles establishing boundaries, and utilizing support networks that are available.